2015
DOI: 10.7883/yoken.jjid.2014.229
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and Characterization of <i>Campylobacter</i> Strains from Diarrheal Patients in Central and Suburban Bangkok, Thailand

Abstract: SUMMARY: Campylobacter-induced diarrhea is increasingly recognized worldwide. However, little information is available regarding the Campylobacter strains associated with diarrheal patients in Thailand. In this study, we attempted to isolate Campylobacter strains from diarrheal patients in Thailand and to characterize the species using a cytolethal distending toxin (cdt) gene-based C. jejuni, C. coli, and C. fetus-specific multiplex PCR assay. Campylobacter species were also confirmed using 16S rRNA gene seque… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
31
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(32 citation statements)
references
References 25 publications
1
31
0
Order By: Relevance
“…The nucleotide sequence of the cdt gene cluster in C. hyointestinalis strain Ch022, an isolate from a patient with diarrhoea in Thailand (Samosornsuk et al, 2015), was analysed by genome walking. A 13 965 bp DNA sequence including the entire cdt gene cluster and its flanking regions was determined as described in Fig.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…The nucleotide sequence of the cdt gene cluster in C. hyointestinalis strain Ch022, an isolate from a patient with diarrhoea in Thailand (Samosornsuk et al, 2015), was analysed by genome walking. A 13 965 bp DNA sequence including the entire cdt gene cluster and its flanking regions was determined as described in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…C. hyointestinalis strain Ch022, isolated from a diarrhoeal patient in Thailand (Samosornsuk et al, 2015), and C. jejuni strains 81-176 (Pickett et al, 1996) and K328 (Kabir et al, 2011) were used in this study. Campylobacter strains were grown on blood agar [blood agar base no.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the phenotypic differentiation is not always accurate. [7][8][9][10]16 To address this shortcoming we optimized a genetic method -the multiplex PCR -to identify the two species, which is more accurate and reliable than the phenotypic test. We used primers for detecting conservative genes: cadF -for all types of Campylobacter genus, hipO -for C. jejuni and asp for C. coli.…”
Section: Introductionmentioning
confidence: 99%
“…Asakura et al have reported that cdt genes are ubiquitously present in C. jejuni, C. coli, and C. fetus and are highly homologous within species but less homologous among species (18; N. Hatanaka, unpublished). Based on these findings, a cdt gene-based multiplex PCR assay for the detection of C. jejuni, C. coli, and C. fetus has been developed (19) and utilized for the identification of these species from poultry and diarrheal patients (20,21). Furthermore, Kamei et al developed a cdtB gene-based PCR-restriction fragment length polymorphism (RFLP) assay for the detection and differentiation of 7 Campylobacter species, i.e., C. jejuni, C. coli, C. fetus, C. hyointestinalis, C. lari, C. helveticus, and C. upsaliensis, and successfully identified the species of 132 Campylobacter strains, failing to identify only 3 C. hyointestinalis strains (22).…”
mentioning
confidence: 99%